Pengaruh Brand Ambassador Refal Hady Terhadap Brand Image Avoskin - Maya Rosmita; Velda Ardia (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This research is motivated by the existence of market growth that offers several products on the market to meet the requirements to meet consumer expectations. Intense competition requires companies to be creative by maximizing the existence of brand ambassadors. The compatibility between the brand and the brand ambassador is very important to support brand communication which in turn can form a good brand image. One of the local skincare brands is Avoskin by collaborating with Refal Hady as the brand ambassador. The purpose of this research 1). Knowing the brand ambassador Refal Hady on Instagram followers @avoskinbeauty. 2). Find out the brand image of Avoskin on Instagram followers @avoskinbeauty. 3). Measuring the influence of brand ambassador Refal Hady on Avoskin's brand image. The theory used in this study is the brand ambassador theory (Transparency, Appropriateness, Credibility and Attractiveness) and brand image theory (Strength, Uniqueness and Profits). This study used a quantitative approach with a survey method, distributing questionnaires to 83 respondents. The results of this study indicate that 1). Brand ambassadors have an average yield of 3.36 with agreement. 2). Brand Image has an average yield of 3.40 with agreement. 3). Brand ambassadors have an influence on brand image of 51.1%, while the other 48.9% comes from other factors outside the research variables.